Solid-State NMR Studies Reveal Native-like β-sheet Structures in Transthyretin amyloid - Lim, Kwang Hun (Biochemistry, 2016)
Structural characterization of amyloid rich in cross-β structures is crucial for unraveling molecular basis of protein misfolding and amyloid formation associated with a wide range of human disorders. Elucidation of the β-sheet structure in non-crystalline amyloid has, however, remained an enormous challenge. Here we report structural analyses of the β-sheet structure in full-length transthyretin amyloid using solid-state NMR spectroscopy. Magic-angle-spinning (MAS) solid-state NMR was employed to investigate native-like β-sheet structures in amyloid state using selective labeling schemes for more efficient solid-state NMR studies. Analyses of extensive long-range (13)C-(13)C correlation MAS spectra obtained with selectively (13)CO- and (13)Cα-labeled TTR reveal that the two main β-structures in the native state, the CBEF and DAGH β-sheets, remain intact after amyloid formation. The tertiary structural information would be of great use for examining quaternary structure of TTR amyloid.